A simplified stoichiometric kinetic model for estimating the concentration of reaction products in anaerobic digestion. Issue 20 (18th October 2017) - Kim, Moonil; Cui, Fenghao
ABSTRACT: Modelling the anaerobic digestion process is often complex and needs to consider many input parameters. This study simplified the modelling procedure by developing an idealized stoichiometric kinetic model that simulates the anaerobic digestion process with only a few parameters: composition coefficients ( α and β ), maximum substrate utilization rate ( q max ), endogenous-decay coefficient ( b ), biodegradable fraction ( fd ), and temperature coefficient ( Ф ). We validated the model with the operating results of a pilot two-phase anaerobic digester for food wastewater disposal and calculated using the MATLAB programing software. The comparison between the experimental and model simulation results demonstrated a good agreement. The developed model correctly simulated the fate of chemicals in the anaerobic digestion process.